Evaluation of Bcl2 gene expression in MCF-7 Human Breast Cancer Cells under treatment of Centaurea Behen extract and Cisplatin - Entezari, Maliheh; Sheikhan, Somayeh; Khazaie, zeinab (Archives of Advances in Biosciences, 2018)
Introduction: Breast cancer is among the most common malignancies of human around the world. Millions of cases of cancer worldwide occur annually, which, if detected in a timely manner, are easier to treat and can be conveniently controlled. In 2008, about 1,384,155 breast cancer cases were detected worldwide, with about 459,000 of them deceased.Method:MTT assay was performed to evaluate cell proliferation.The BCL2 gene is an inhibitor of apoptosis that prevents the release of cytochrome C from mitochondria and leads to inhibition of various apoptosis stimuli. Due to the importance of this gene in the apoptotic process, the level of BCL2 gene expression under treatment of Cisplatin and Centaurea Behen agents for 24 hours and 48 hours was evaluated in this research,using the Real time-PCR method. It is noteworthy that Cisplatin as a DNA binding agent may be effective in treating breast cancer;moreover, some studies have shown that Centaurea Behenplant has an antioxidant effect that can be a preventive factor in cancer.Results: The results obtained related to Cisplatin showed that IC50 for cells treated with Cisplatin for 24 hours was about 2.91 mg/ml while IC50 for cells treated with Cisplatin for 48 hours was about 1.77 mg/ml. Similarly, results obtained related to Centaurea Behenherbal extract showed that IC50 for cells treated with Centaurea Behen for 24 hours was about 9.64 mg/ml while IC50 for cells treated with Centaurea Behen for 48 hours was about 7.85 mg/ml.Results showed that the expression level of gene under treatment of the Cisplatinand Centaurea Behenhas decreased compared to the non-treatment state, so this expression reduction showed a significant difference between samples group and control group . .